2016
DOI: 10.5505/bsbd.2016.70299
|View full text |Cite
|
Sign up to set email alerts
|

Quality Of Life And Healthy Life Style Before Coronary Artery Bypass Graft Surgery

Abstract: bsbd@balikesir.edu.tr www.bau-sbdergisi.com ÖZET AMAÇ: Bu çalışmanın amacı koroner arter bypass greft (KABG) cerrahisi planlanan hastaların yaşam kalitesini değerlendirmektir. YÖNTEMLER: Tanımlayıcı prospektif olarak yürütülen çalışmanın örneklemine KABG cerrahisi planlanan 118 hasta alınmıştır. Verilerin toplanmasında hastanın demografik ve tıbbi öyküsünden, yaşam kalitesini değerlendirmek üzere SF36 ve sağlıklı yaşam biçimi ölçeğinden yararlanılmıştır. Verilerin istatistiksel analizlerinde sayı, yüzde, ortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…It has been reported that higher education levels are associated with better knowledge of CVD, fewer risk factors and health-related behavioral changes. Similarly, in other studies conducted on the subject, it has been shown that patients with a high level of education have higher average healthy lifestyle scores [17,19,27]. These results show that socioeconomic level is important in increasing the knowledge level of risk factors related to cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 69%
“…It has been reported that higher education levels are associated with better knowledge of CVD, fewer risk factors and health-related behavioral changes. Similarly, in other studies conducted on the subject, it has been shown that patients with a high level of education have higher average healthy lifestyle scores [17,19,27]. These results show that socioeconomic level is important in increasing the knowledge level of risk factors related to cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 69%
“…The number of CABG performed patients in Turkey is thought to increase every day, but the exact number is unknown (Demir Korkmaz et al, 2015). This procedure is generally performed with two techniques such “On‐Pump” which is performed with the use of a cardiopulmonary bypass machine and “Off‐Pump” in which the heart continues to provide blood to the rest of the body during the procedure (Dirimeşe et al, 2016; Lamy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The number of CABG performed patients in Turkey is thought to increase every day, but the exact number is unknown (Demir Korkmaz et al, 2015). This procedure is generally performed with two techniques such "On-Pump" which is performed with the use of a cardiopulmonary bypass machine and "Off-Pump" in which the heart continues to provide blood to the rest of the body during the procedure (Dirimeşe et al, 2016;Lamy et al, 2016).The purpose of CABG surgery is to eliminate/alleviate certain symptoms (shortness of breath, sleep problems, surgical pain, and fatigue) associated with coronary artery disease, thereby improving the quality of life and reducing the risk of myocardial infarction (Pačarić et al, 2020;Tsai et al, 2019). However, it is a stressful, undesirable,…”
mentioning
confidence: 99%
“…In a study where the healthy lifestyle behaviours of elderly individuals were examined based on different variables, male participants had higher levels of healthy lifestyle behaviours compared to female participants 30 . In another study, it was also determined that the mean healthy lifestyle behaviour score of men was higher than that of women 31 . Similarly, studies conducted on the same topic in Iran found higher mean healthy lifestyle behaviour scores among men in comparison to women 23,32 .…”
Section: Discussionmentioning
confidence: 99%